A novel energy regenerative shock absorber for in-wheel motors in electric vehicles. (1st December 2022) - Salman, Waleed; Zhang, Xingtian; Li, Hai; Wu, Xiaoping; Li, Ning; Azam, Ali; Zhang, Zutao
Highlights: A regenerative shock absorber in in-wheel motors was proposed for the first time. Potential to convert irregular vibrations of running vehicles to electrical power. A novel motion rectifier was designed and manufactured. A high-power output of 380 W with an efficiency of 62% was achieved. Abstract: As the demand for energy harvesting increases, regenerative shock absorbers have received more attention in expanding the cruising range of electric vehicles. The current study proposes a novel design of regenerative shock absorber for the in-wheel motor to capture the vibration energy from the rough road surface while driving an electric vehicle. The regenerative shock absorber design mainly focuses on vibration capture, motion transmission, and generator modules. The motion-capture module collects the irregular vibrations caused by the roughness of the road surface. The motion transmission module transfers linear motion to unidirectional rotational motion, which is then converted to electrical power in the generator module by mechanical gears and clutches. The purpose of using an auxiliary generator is to improve production capacity while also controlling the damping process of the shock absorber. Also, the inclusion of a supercapacitor and voltage regulator improves the stability of the charging circuit. An electro-mechanical Instron testbed was employed for the experimental study to verify the simulated results and found a good agreement. The experimental results demonstrated that the generated power from two generators was >380 W with an efficiency of 62%. The proposed regenerative shock absorber is effective and feasible for renewable energy applications in electric vehicles.